Enhancing basic education through transmedia: Using media for teaching in Blumenau/SC-Brazil - Geisler, Maeles Carla; Bona, Rafael José; Galarça, Sandro Lauri da Silva (Seven Editora, 2024)
The overall aim of this article is to present educational proposals focusing on transmedia in education in the municipality of Blumenau/SC. Transmedia refers to the practice of expanding a narrative or content across multiple platforms, allowing for a more immersive and interactive experience for the public. The research is classified as exploratory, descriptive, with a qualitative approach, and is being carried out in the Postgraduate Program in Education (PPGE/Furb). As a result of the work, two distinct proposals emerged: one with video production and another with podcast production, both focused on transmitting cultural elements of the city. The aim is to encourage teachers to reflect on the use of media in education, increasing student engagement. It is hoped that these innovative approaches will enrich teaching and promote learning that is connected to local culture. The study thus seeks to stimulate the adoption of more dynamic and contemporary pedagogical practices in Blumenau schools, fostering interaction between media and education. DOI:https://doi.org/10.56238/sevened2024.015-003